Are smokers who are regularly exposed to e-cigarette use by others more or less motivated to stop or to make a quit attempt? A cross-sectional and longitudinal survey - Sarah E. Jackson; Emma Beard; Susan Michie; Lion Shahab; Tobias Raupach; Robert West; Jamie Brown (BMC Medicine, 2018)
Abstract Background Concerns have been raised that observing other people using e-cigarettes may undermine motivation to quit by renormalising smoking. This study aimed to explore associations between regular exposure to other people’s e-cigarette use and motivation to stop smoking and quit attempts in smokers. Methods Data were from 12,787 smokers in England who participated in the Smoking Toolkit Study between November 2014 and May 2018. At baseline, respondents were asked whether anyone other than themselves regularly used an e-cigarette in their presence, whether they had made a quit attempt in the past year and how motivated they were to stop. Data at 6-month follow-up were available for 1580 respondents, who reported on whether they had attempted to quit in the past 6 months. Results Smokers who reported regular exposure to e-cigarette use by others were more likely than those who did not to have tried to stop smoking in the past year (32.3% vs. 26.8%; unadjusted RR 1.21, 95% CI 1.11–1.31) and have high motivation to quit (16.6% vs. 14.2%; unadjusted RR 1.17, 95% CI 1.05–1.30) but were not significantly more or less likely to make a quit attempt over the subsequent 6 months (34.4% vs. 31.3%; unadjusted RR 1.10, 95% CI 0.88–1.38). In models that adjusted for participants’ own current e-cigarette use and unadjusted and adjusted models excluding current e-cigarette users from the sample, there were no significant associations between exposure to e-cigarette use by others and past quit attempts (RR 0.97–1.00), high current motivation to quit (RR 0.97–1.00) or prospective quit attempts (RR 0.94–1.12). In contrast, exposure to use of cigarettes was associated with low motivation to quit even after adjustment (RR 0.89) but not with quit attempts. Participants’ own use of e-cigarette was strongly associated with high motivation to quit (RR 1.95) and past quit attempts (RR 2.14) and appeared to account for the bivariate associations with reported exposure to e-cigarettes. Conclusion Smokers who report regular exposure to other people using e-cigarettes are more likely to report past quit attempts and high current motivation to quit, but there does not appear to be an independent association with motivation or quit attempts after adjustment for their own current use of e-cigarettes. In contrast, reported exposure to other people using cigarettes was independently and negatively associated with high motivation.